Ijtihad From Friends Of The Prophet Muhammad In Making Justice Law - Hidayat, Nur; Jafar, Wahyu Abdul (International Journal of Educational Research & Social Sciences, 2021)
This study explains that ijtihad existed when the companions of the Prophet Muhammad were still alive and continued to develop along with the development of Islam. Ijtihad was born because it is a logical reflection of the struggles of various situations in society that require solutions to be found. However, it should be noted that not everyone can perform ijtihad because ijtihad must use the science of ushul fiqh. Ijtihad, which is carried out carelessly can produce a perverted legal product, as is the case today. Therefore, through this study, the author discusses the ijtihad practised by the companions of the Prophet Muhammad before the emergence of the science of ushul fiqh. The purpose of this discussion is to find out whether the licensed products that were born before the emergence of ushul fiqh science are legally flawed or not. After conducting an in-depth study, it was found that even though at that time the science of ushul fiqh had not been recorded in one book, the companions of the Prophet Muhammad were able to formulate and produce Islamic law products precisely. This happens because they master the science of ushul fiqh and keep it well in their memory.